2014
DOI: 10.1007/s10535-014-0449-y
|View full text |Cite
|
Sign up to set email alerts
|

Marker assisted gene pyramiding for enhanced Tomato leaf curl virus disease resistance in tomato cultivars

Abstract: The present research is aimed towards molecular marker assisted pyramiding Tomato leaf curl virus (ToLCV) disease resistance genes into two ToLCV susceptible tomato (Solanum lycopersicum L.) cvs. Pbc and H-86 (resistance genes recipient parents). Resistance gene donors were EC-538408 (Solanum chilense) and EC-520061 (S. peruvianum) in the case of cv. Pbc, and EC-520061 (S. peruvianum) and H-24 (S. lycopersicum) in the case of cv. H-86. A ToLCV resistance gene associated co-dominant simple sequence repeat (SSR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Nevertheless, if efficient spread to tomato occurs, here we showed that the Ty-1 gene already deployed for the control TYLCD-associated viruses [49] seems to provide resistance to ToLCNDV, even for the isolate from India that causes severe infections in susceptible tomatoes. Moreover, other gene combinations have been reported to provide effective resistance to ToLCNDV infections in tomato [50,51]. …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, if efficient spread to tomato occurs, here we showed that the Ty-1 gene already deployed for the control TYLCD-associated viruses [49] seems to provide resistance to ToLCNDV, even for the isolate from India that causes severe infections in susceptible tomatoes. Moreover, other gene combinations have been reported to provide effective resistance to ToLCNDV infections in tomato [50,51]. …”
Section: Discussionmentioning
confidence: 99%
“…Wild crop relatives harbor novel and exotic genetic resources that are crucial for the development of insect pest management (Hajjar and Hodgkin, 2007 ). Some wild species have been applied in breeding practices, such as for tomato (Vidavski et al, 2008 ; Kumar et al, 2014 ). G. soja is widely distributed in China, Korea, Japan, and Northeast Russia, and long-term exposure to various environmental stresses in the wild has rendered G. soja able to adapt to diverse environments with severe abiotic and biotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…As one example, five Ty genes exhibiting varying degrees of resistance to tomato yellow leaf curl virus (TYLCY) were successfully introgressed into cultivated varieties (Ji, Scott, Hanson, Graham, & Maxwell, 2007;Menda et al, 2014). Pyramiding of these Ty genes from different wild tomatoes has contributed to durable and broad resistance to TYLCY (Kumar, Tiwari, Datta, & Singh, 2014;Vidavski, Czosnek, Gazit, Levy, & Lapidot, 2008).…”
Section: Biotic Stress Tolerancementioning
confidence: 99%